Relation of hs-CRP and Glycogen phosphorylase BB in Acute Myocardial Infarction Patients - Neelima singh; Chanchal Garg; Puneet Rastogi; Rakesh Shah; Vedika Rathore; Roshan Kumar Mahat; Prerna Vyas Gokhle (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background: Inflammation has important role in the pathophysiology of atherosclerosis and acute myocardial infraction and hs-CRP is an inflammatory marker. GPBB is a marker of myocardial necrosis or myocardial ischmia i.e. the initial phase of AMI. The aim of this study was to know the levels of GPB and the relation between hs-CRP and GPBB in AMI patients.  Materials & methods: This study was conducted in the Cardiology of J.A. Hospital and Department of biochemistry, G.R. Medical College, Gwalior. Patients were admitted with severe chest pain out of which 100 were included in this study. 50 normal healthy individuals were also selected. Blood samples were collected at the admission time for the analysis of hs-CRP and GPBB. All patients underwent thorough clinical examination and investigations. Estimation of GPBB and hs-CRP were done by ELISA method and other routine parameters done by enzymatic method.  Results: The mean level of GPBB in patients was 46.92ng/mL while in controls it was 13.88ng/mL. The mean level of hs-CRP in patients was 4.38mg/L while in controls it was 1.34mg/L. There was highly significant difference of GPBB and hs-CRP in control group and AMI group. The finding of results showed that hs-CRP and GPBB was positively correlated. The levels of FBG, Triglyceride, Cholesterol, LDL, and VLDL were significantly increased and HDL was decreased in AMI group when compare controls. Conclusion: Our results demonstrate that there was positive correlation of hs-CRP and GPBB in AMI patients. So along with GPBB, hs-CRP is also additional marker of myocardial ischemia and AMI.